Design Build Competition Strategy to Improve Project Execution in PT Kilang Pertamina International - Mulyadi, Hendrikawan; Novani, Santi (International Journal Labs, 2023)
PT KPI is the refining & petrochemical sub-holding company of PT Pertamina (Persero) that acts as a strategic holding company. PT KPI makes investments and runs Pertamina’s businesses in refining oil and gas and other materials to make high-value fuel, lubricant, petrochemical, and pharmaceutical products. Based on PT. KPI experiences, offently projects suffer delays and cost overruns which affect the quality of the project. This study aimed to evaluate the project execution strategy Design Build Competition (DBC) as strategy to improve project execution. This study starts with the identification of the issue, followed by data collection which covers primary and secondary data, after that the series of data were analyzed using Analytical Hierarchy Process (AHP). The results showed that DBC strategy is the solution for PT. KPI to improve the execution of the project mainly in terms of duration and quality. The conclusion and recommendation of the study are that in order successfully executed DBC, PT. KPI should engage several strategic decisions which include organizational restructuring, resource allocation, and stakeholder management.